2013
DOI: 10.4103/0253-7613.111903
|View full text |Cite
|
Sign up to set email alerts
|

Metronidazole induced cerebellar ataxia

Abstract: Metronidazole is a widely used antimicrobial usually prescribed by many specialist doctors for a short duration of 10-15 days. Prolonged use of metronidazole is rare. The present case is of a patient who used the drug for 4 months and developed peripheral neuropathy, convulsions, and cerebellar ataxia. He was treated with diazepam and levetiracetam. The patient recovered completely following discontinuation of metronidazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Mostly, a dose above 1 g/day for at least 30 days or total dosage of 50 g can result in cerebellar ataxia. [16] Our data revealed that the occurrence of MIE is 8.6% for those cancer patients who receive totally >30-g metronidazole. The prolong use with more cumulative doses of oral form metronidazole therapy revealed a greater opportunity to develop MIE.…”
Section: Discussionmentioning
confidence: 80%
“…Mostly, a dose above 1 g/day for at least 30 days or total dosage of 50 g can result in cerebellar ataxia. [16] Our data revealed that the occurrence of MIE is 8.6% for those cancer patients who receive totally >30-g metronidazole. The prolong use with more cumulative doses of oral form metronidazole therapy revealed a greater opportunity to develop MIE.…”
Section: Discussionmentioning
confidence: 80%
“…A case of metronidazole-associated cerebellar ataxia was described by Hari et al in 2013 [ 6 ] in which a 31-year-old male with an amebic liver abscess developed gait instability after 4 months of metronidazole therapy. MRI findings included a strikingly similar appearance to the case presented here with symmetric nonenhancing punctate foci of increased T2 signal in the pons bilaterally, facial nuclei, and dentate nuclei [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metronidazole can cause cerebellar toxicity when used for a prolonged duration of treatment, typically over 6 weeks to several months [76,77]. Symptoms can include ataxia, paresthesias, slurred speech, hypotonia, seizures, and nystagmus [76,77].…”
Section: Antimicrobials Metronidazolementioning
confidence: 99%
“…Metronidazole can cause cerebellar toxicity when used for a prolonged duration of treatment, typically over 6 weeks to several months [76,77]. Symptoms can include ataxia, paresthesias, slurred speech, hypotonia, seizures, and nystagmus [76,77]. Brain MRI can show evidence of toxicity with hyperintensities on T2 and FLAIR in the dentate nuclei, nodularity in the cerebellar parenchyma on T2, or cerebellar edema with increased diffusion coefficients [76][77][78][79][80].…”
Section: Antimicrobials Metronidazolementioning
confidence: 99%